Increasing Educational Capacity as an Effort to Achieve SDGs 2030 for Village Association Personnel - Rivo Nugroho; Wiwin - Yulianingsih; Gunarti Dwi Lestari; Sujarwo Sujarwo; Narong Kiettikunwong (Journal of Nonformal Education, 2023)
To realize the mandate of Law Number 20 of 2003 concerning the National Education System and Law of the Republic of Indonesia Number 12 of 2012 concerning higher education, namely to provide the widest opportunity for every individual to pursue formal, non-formal, and informal education through lifelong learning facilities as well as providing equal opportunities for certain qualifications as an effort to improve the quality of human resources and realize the 2030 SDGs regarding the provision of quality education, a Prior Learning Recognition program was held by Education Personnel Education Institutions for the community to be able to continue formal education to a higher level which in the end is the provision of proof of learning outcomes in the form of a diploma. Therefore, this research was conducted to describe and analyze the process of strengthening the synergy of Education Personnel Education Institutions in implementing the Recognition of Prior Learning (RPL) program for Village Companions, Ministry of Villages, Development of Disadvantaged Regions and Transmigration (Kemendes PDTT) with Bojonegoro Regency at Surabaya State University and State University Yogyakarta. The research method applied is a qualitative method with a case study approach. Data collection techniques used were observation, interviews, and documentation for program administrators, lecturers, and students. The data analysis technique used is the Miles and Huberman model which consists of 4 stages, namely the stages of collection, reduction, presentation, and concluding the research data that has been obtained. The results obtained from the research that strengthen synergy are carried out by organizing higher education programs in non-formal education study programs, research, and empowering the community by LPTKs at Surabaya State University and Yogyakarta State University. The results of the analysis of the implementation of the Recognition of Prior Learning program were obtained by applying a SWOT analysis. And it can be concluded that the implementation of the Recognition program for past learning of Village Facilitators of the Ministry of Village, PDTT with Bojonegoro Regency can improve the quality of human resources.